State, Institutional Activists, and Social Organizations: Social and Solidarity Economy Policies in the Municipality of Almirante Brown, Argentina (2019–2023). (Desarrollo, Estado y Espacio, 2025)
The aim of this research is to analyze the processes of design and implementation of municipal Social and Solidarity Economy policies, focusing on the relationship established between state institutions and social organizations that emphasize territorial identity and support self-managed forms of work. The empirical reference is a case study in the Municipality of Almirante Brown, Buenos Aires, Argentina, during the period 2019-2023, observing the implementation of policies at the interfaces between state and non-state spaces where public managers and members of social organizations interact and operate. As a theoretical framework, we understand the state as an arena of conflicts and power relations. We engage with the concepts of institutional activists, the duality of field-level state agents, and government activism, which emphasizes conflicts within the state field. The research methodology involved the analysis of primary sources (semi-structured interviews, field observation) and secondary sources (academic literature, public documents, and official statistics). Among the results, we challenge the common assumption that simplistically separates the state sphere from that of social organizations, reducing their relationship to situations of co-optation or autonomy. Additionally, we observe how the relationships between public managers and organizations are activated in the field of policy design and implementation, as part of the conflicts and alliances among various groups within the public administration.
Keywords: State; Social Organizations; Public Policies; Argentina